Business accounting 1 - Wood, Frank; Sangster, Alan (London: Pearson Education Ltd, 2012)
This is the latest edition of the world's best-selling textbook on bookkeeping and accounting. It contains a large number of questions and answers and worked examples
Includes index
eng.
Keywords: Financial analysis; Financial statements; Accounting equation; Financial reporting